PERSEPSI SISWA TENTANG LAYANAN PENGUASAAN KONTEN DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI SMP NEGERI 3 MUARA BUNGO - Erpita E (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2021)
This research is motivated by students who have low learning achievement such as: have no desire to learn, are more interested in helping their parents and playing with their friends, school assignments are only simple work, there is no effort in doing the work or assignments given. The purpose of this study was to see students' perceptions of content mastery services in improving student achievement. This research method is descriptive quantitative. The population in this study were students of class VIII at SMP N 3 Muara Bungo totaling 227 people, the sample obtained was 90 people who were selected by simple random sampling technique. The instrument used is a questionnaire. The data were analyzed using percentages. The research findings show that mastery of content in improving student achievement is of good quality (83%), to clarify several indicators can be divided, namely indicators: (1) motivating learning is of good quality (83%) , (2) attitudes and study habits are of good quality (83%), and (3) improving learning skills are of good quality (82%). The implication of this research is that it can be used as an analysis of student needs to help direct BK teachers in providing services at SMP Negeri 3 Muara Bungo.